Analisis Efisiensi Teknis Perkebunan Kakao Sumatera Utara Dengan Pendekatan Stochastic Frontier (SFA) - Lamhot Gibson Halashon Pane (Jurnal Analisis Riset, Statistik dan Komputasi, 2023)
The global cocoa supply deficit opens up oppurtunities for Indonesia to encourage and make cocoa one of the mainstay export commodities.Cocoa producing center provinces in Indonesia have the oppurtunity to achieve it. However, North Sumatera as one of the largest cocoa been production has not yet reached optimal production. The solution to that problem is improving productivity through increasing technical efficiency. This study aims to analyze technical efficiency of cocoa production and variables that effect the technical inefficiencies of smallholder cocoa farmers in North Sumatera Province using raw data of cocoa strategic commodity survey 2019. Obervation units in this study were 1,478 smallholder cocoa farmers. The analysis method uses a parametric approach, nameley Stochastic Frontier Analysis (SFA). The results of SFA, showed the mean technical efficiency of cocoa farmers of 0.6069, that means, in generally cocoa farmers are technically inefficient . The factors that significantly influence inefficiency of cocoa farming are planting distance, diversification crops, fermented cocoa beens, farmer groups, and source of income for farmers.